‘Kongsi Rezeki’ charity programme for UMP undergraduates - UMP, PNC (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) carried out a ‘Kongsi Rezki’ programme which was a really low-priced lunch take-away aimed at helping to lessen the financial burden of needy undergraduates.